The oxidative degradation of barley β-glucan in the presence of ascorbic acid or hydrogen peroxide. (5th June 2015) - Mäkelä, Noora; Sontag-Strohm, Tuula; Maina, Ndegwa Henry
Highlights: HPSEC and AsFlFFF were used to analyse oxidative degradation of barley β-glucan. Compared to ascorbic acid, hydrogen peroxide caused more degradation of β-glucan. The formation of aggregates in oxidised samples was seen with AsFlFFF. The compact aggregates suggest more interactions between oxidised β-glucans. Abstract: Cereal β-glucans are polysaccharides with health benefits that have been linked to their ability to increase luminal viscosity. However, the functional properties of cereal β-glucans may be diminished by the susceptibility of this polysaccharide to oxidative degradation. In this study, barley β-glucan was oxidised with hydrogen peroxide or ascorbic acid and the oxidative degradation of β-glucan was investigated using both asymmetrical flow field-flow fractionation (AsFlFFF) with aqueous solvent and high performance size exclusion chromatography (HPSEC) with LiBr in DMSO as the solvent. Oxidation was shown to cause degradation of β-glucan, the reaction being faster when oxidised with hydrogen peroxide compared with ascorbic acid. Both HPSEC and AsFlFFF showed comparable results as long as aggregates (only observed in AsFlFFF) were not included in the integration. The compact aggregates observed in oxidised samples suggest oxidation driven interactions between β-glucan molecules.